Відповідальна комунікація – актуальна потреба користувачів Інтернету - Пелещишин, Андрій; Корж, Роман (Видавництво Львівської політехніки, 2013)
In this paper we show the trends of social information needs transformation under technological conditions and set a new actual need of society – the need for responsible communication in the Internet information space.
Keywords: Інтернет; форуми; віртуальні спільноти; інформаційні потреби; інформаційна діяльність; соціально-інформаційні інтерфейси